2011
DOI: 10.1111/j.1525-1446.2011.00988.x
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Nurses’ Knowledge of Botulism

Abstract: The results of this study indicate the need for an assessment of the current education nurses receive about botulism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…The mean percentage of correct answers for the samples was 25.95%, with a SD of ±19.89%. [11] Whereas the mean percentage of correct answers for this study was 14.79% and less than mentioned study. However, results of both studies showed poor knowledge of nurses about bioterrorism.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…The mean percentage of correct answers for the samples was 25.95%, with a SD of ±19.89%. [11] Whereas the mean percentage of correct answers for this study was 14.79% and less than mentioned study. However, results of both studies showed poor knowledge of nurses about bioterrorism.…”
Section: Discussioncontrasting
confidence: 63%
“…The findings like other studies showed that the education is helpful and important for increasing the amount of preparation, knowledge, and practice of nurses and other health staff. [81112142325] It also became clear that education is effective on nurses′ knowledge in all areas of bioterrorism such as the concept and nature of bioterrorism, the bioterrorism causal factors, the release of bioterrorism factors, bioterrorism detection, and decontamination of victims. Like this study, the results of a study that assess the effect of bioterrorism education on knowledge, preparedness, and ability to deal with biological agents demonstrated that achieving the purpose of the bioterrorism preparedness is directly related to educated people like nurses as the first responders of such incidents and are able to quickly identify infectious agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the existing nurses and other health staff in health care facilities should not be ignored. Continues education courses are vital for increasing the level of preparedness, awareness, and practice of this target group (4,14,17,18,20,(25)(26)(27).…”
Section: Resultsmentioning
confidence: 99%
“…Considering that in biological terrorism, hospitals, emergency departments and health practitioners, including physicians and nurses, are the first responders dealing with patients, they are more responsible, and having bioterrorism preparedness training program will be necessary (15,16). Recent studies have shown that nurses have poor knowledge in dealing with biological agents (17)(18)(19)(20). Another study from America was carried out to assess the nurses' preparedness against bioterrorism and determined that most participants did not have enough knowledge to respond in these situations.…”
Section: Introductionmentioning
confidence: 99%